PRP-loaded hydrogel for rotator cuff repair by promoting osteogenic differentiation and tendon regeneration - Zhang, Ru-Sen; Zheng, Zhi-Yang; Zhu, Guo-Qing; Luo, Chao-Rong; Yuan, Jing-Min; Ye, Yi-Lin; Zhuang, Ze-Qin; Liu, Ze-Zheng; Li, Qing-Chu; Huang, Xi-Zhao (Frontiers in Bioengineering and Biotechnology, 2025)
ObjectiveRotator cuff injuries are a common and challenging shoulder joint pathology that significantly impacts shoulder function and quality of life. Current treatments, particularly arthroscopic repair, face high failure rates due to the difficulty of regenerating the native tendon-bone interface. This study aimed to develop and evaluate a platelet-rich plasma–carboxymethyl chitosan–tannic acid composite hydrogel (PRP-CMCS-TA), designed to address these limitations and enhance the repair and regeneration of the tendon-bone interface.MethodsThe composite hydrogel was synthesized by creating a CMCS-TA hydrogel via chemical cross-linking, which was then integrated with PRP. Its functionality was assessed through a series of in vitro biocompatibility, bioactivity, and sustained-release assays, and its efficacy in promoting tendon-bone interface regeneration was evaluated in a rat rotator cuff injury model using micro-CT, biomechanical testing, and histological analysis.ResultsIn vitro experiments demonstrated the biocompatibility and bioactivity of PRP-CMCS-TA. The hydrogel supported cell viability and proliferation, and sustained the release of PRP components, which are critical for promoting tenogenic and osteogenic differentiation. The in vitro results indicated that PRP-CMCS-TA could provide a suitable environment for cell growth and tissue repair. In vivo studies were conducted using a rat rotator cuff injury model. The model was divided into three groups: Control, CMCS-TA, and PRP-CMCS-TA. Micro-CT scans and histological analyses were performed at predetermined time points to evaluate the repair capability of the composite hydrogel. The results showed that PRP-CMCS-TA significantly promoted bone regeneration and achieved superior tendon-bone interface repair compared to the other groups.ConclusionThe PRP-CMCS-TA composite hydrogel exhibits good biocompatibility and effectively repairs the tendon-bone interface by promoting osteogenic differentiation and tendon regeneration. This study provides new insights into the application of bioactive materials for rotator cuff injuries and offers a promising strategy for improving the outcomes of rotator cuff repair. Further research and clinical trials are needed to translate these findings into practical applications and to establish the hydrogel as a standard treatment option for rotator cuff injuries.